Clinical and endoscopic features of primary small bowel lymphoma: a single-center experience from mainland China - Tian, Feng-Yu; Wang, Jue-Xin; Huang, Gang; An, Wen; Ai, Li-Si; Wang, Sui; Wang, Pei-Zhu; Yu, Yan-Bo; Zuo, Xiu-Li; Li, Yan-Qing (Frontiers in Oncology, 2023)
Objective: The worldwide incidence of primary small intestinal lymphoma (PSIL) is increasing. However, little is known about the clinical and endoscopic characteristics of this disease. The aim of this study was to investigate the clinical and endoscopic data of patients with PSIL, with the goal of enhancing our understanding of the disease, improving diagnostic accuracy, and facilitating more accurate prognosis estimation. Methods: Ninety-four patients diagnosed with PSIL were retrospectively studied at Qilu Hospital of Shandong University between 2012 and 2021. The clinical data, enteroscopy findings, treatment modalities, and survival times were collected and analyzed. Results: Ninety-four patients (52 males) with PSIL were included in this study. The median age of onset was 58.5 years (range: 19-80 years). Diffuse large B-cell lymphoma (n=37) was the most common pathological type. Abdominal pain (n=59) was the most frequent clinical presentation. The ileocecal region (n=32) was the most commonly affected site, and 11.7% of patients had multiple lesions. At the time of diagnosis, the majority of patients (n=68) were in stages I-II. A new endoscopic classification of PSIL was developed, including hypertrophic type, exophytic type, follicular/polypoid type, ulcerative type, and diffusion type. Surgery did not show a significant increase in overall survival; chemotherapy was the most commonly administered treatment. T-cell lymphoma, stages III-IV, "B" symptoms, and ulcerative type were associated with poor prognosis. Conclusions: This study provides a comprehensive analysis of the clinical and endoscopic features of PSIL in 94 patients. This highlights the importance of considering clinical and endoscopic characteristics for accurate diagnosis and prognosis estimation during small bowel enteroscopy. Early detection and treatment of PSIL is associated with a favorable prognosis. Our findings also suggest that certain risk factors, such as pathological type, "B" symptoms, and endoscopic type, may affect the survival of PSIL patients. These results underscore the need for careful consideration of these factors in the diagnosis and treatment of PSIL.